The Profitability of Momentum Strategies : A Study of Indonesian Stock Exchange - Mosii, Rakhmat Luthfiansyah; Wibowo, Sigit Sulistiyo (UI Scholars Hub, 2019)
We investigate the profitability of style and price momentum strategy in the Indonesian stock market from the year 2000 to 2015. We find the style momentum strategy yields significant positive returns while the price momentum strategy tends to produce negative returns. This result confirms the findings of Lewellen (2002) that style momentum returns are generally stronger than the conventional momentum. The average monthly returns of the double-sorted size-B/M style momentum are ranging from 1.98% to 2.64% and persistent after controlling for market factor using JSX index. Our findings suggest investors should utilize publicly available information such as size and book-to-market ratio on their investment decision in the Indonesian stock market.